CORRELATION OF 24-HOUR URINARY PROTEIN TO SPOT URINARY PROTEIN TO CREATININE RATIO AT DIFFERENT TIMES OF THE DAY IN PATIENTS WITH CHRONIC KIDNEY DISEASE - SABIR , O; BASIT, MB; RIAZ, MM; SHAHID, AH; QADRI, GA; TARIF, N (Biological and Clinical Sciences Research Journal, 2023)
Spot urine protein to creatinine ratio has become a conventional measure of daily protein excretion in patients with chronic kidney disease (CKD). It is easily obtained and is reproducible. However, the values may vary with the time of the day, and collecting the first-morning void is typical. Twenty-four hours of urinary protein has been the traditional gold standard test for estimating protein excretion. This test is still carried out in centers where spot measurements are unavailable. We conducted our study to determine the correlation between 24-hour urinary protein and spot urinary protein to creatinine ratio at different times of the day (early morning, afternoon, and night). Sixty-seven patients of CKD fulfilling the inclusion criteria were asked to provide 24-hour urine samples according to standard recommendations. According to protocol, small aliquots of urine samples (5 ml each) were taken from the 24-hour sample to be processed for spot urinary protein and creatinine. Data was analyzed on SPSS version 22 and is presented as numbers, means + SD (age, spot urinary protein to creatinine ratio for morning, afternoon, and night), and frequencies (gender, type of kidney disease). Pearson's 'r' was tested for a significant correlation between 24 hours of urine protein and all different samples of spot collections. In contrast, sensitivity and specificity for spot urine protein-to-creatinine ratio predicting 24-hour protein excretion of <1, 1 – 3.5, and >3.5 g/day were determined using receiver operating characteristic curves (ROC Curves). In our cohort of patients across all stages of chronic kidney disease, we observed that there was a strong correlation between all three protein-to-creatinine ratio samples with 24 hours of urinary protein excretion; however, nighttime protein creatinine ratio showed the strongest correlation with 24 hours of urinary protein excretion (Pearson's r: 0.797). Nighttime spot urine protein to creatinine ratio sample was also found to have the highest sensitivity across all 24-hour urinary protein excretion levels.A nighttime spot urinary protein to creatinine ratio sample may reliably predict 24 hours of urinary protein excretion.